2016
DOI: 10.1038/gt.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of an RNA trans-splicing molecule suitable to repair a large number of COL7A1 mutations

Abstract: RNA trans-splicing has become a versatile tool in the gene therapy of monogenetic diseases. This technique is especially valuable for the correction of mutations in large genes such as COL7A1, which underlie the dystrophic subtype of the skin blistering disease epidermolysis bullosa. Over 800 mutations spanning the entire length of the COL7A1 gene have been associated with defects in type VII collagen, leading to excessive fragility of epithelial tissues, the hallmark of dystrophic epidermolysis bullosa (DEB).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The procedure of western blotting was performed as previously described. 13 , 43 Ponceau red (Sigma-Aldrich) staining of the membrane was performed after electro-blotting. For detection of type VII collagen a rabbit anti-type VII collagen antibody (kindly provided by Dr. Alexander Nyström, Freiburg, Germany) was used at a dilution of 1:3,000 in Tris-buffered saline with 0.2% Tween (TBS-T) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of western blotting was performed as previously described. 13 , 43 Ponceau red (Sigma-Aldrich) staining of the membrane was performed after electro-blotting. For detection of type VII collagen a rabbit anti-type VII collagen antibody (kindly provided by Dr. Alexander Nyström, Freiburg, Germany) was used at a dilution of 1:3,000 in Tris-buffered saline with 0.2% Tween (TBS-T) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of western blotting was performed as previously described. 40 , 41 Ponceau red (Sigma-Aldrich, St. Louis, MO, USA) staining of the nitrocellulose membrane was performed after electro-blotting. Nitrocellulose membrane was blocked with blocking reagent (Roche Diagnostics, Mannheim, Germany) diluted 1:10 in Tris-buffered saline with 0.2% Tween (TBS-T) for 1 hr at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies have shown remarkable results in terms of gene correction/excision using both in vivo and ex vivo approaches. [64][65][66][67][68][69][70] In addition, a previous study of ex vivo gene therapy in an individual with junctional EB demonstrated restoration of laminin 332 expression following retroviralmediated transfection of epidermal stem cells with the LAMB3 gene, with long-lasting phenotypic correction in the grafted skin. 71 A US trial is currently evaluating the safety and efficacy of a retroviral vector and genetically engineered epithelial graft cultured from the skin of patients with RDEB (ClinicalTrials.gov identifier: NCT01263379).…”
Section: Gene Therapymentioning
confidence: 96%